Eksploring Basic Movements of Early Childhood in Kindergarten - Yaswinda, Yaswinda; Bakhtiar, Syahrial; Maulana, Ihsan; Irsakinah, Irsakinah (Indonesian Journal of Early Childhood Education Studies, 2021)
This research is based on the increasingly distant children from physical activity. Though very physical literacyimportant to develop and will have a bad impact if not developed. The objectives of this study are to analyze literacy development Kindergarten children's physical activities related to basicmotion and knowledge in motion. The method in research was mix method research. The sample (n=30) at three kindergarten in Padang City. The research results that can be concluded are: The basic movements of children in the three Kindergartens studied showed varying scores in the range of medium and high scoresand. Based on this research, the movement ability of children in coastal areas is better than children in hilly areas. It can be concluded that children's movement abilities are influenced by geography at the beginning of the observation, but after repeated basic movement activities, children in high geographic areas can match and even exceed basic movement skills of children in lowlands.